A Semantic Analysis of Meaning Types in Bruno Mars' "Talking to the Moon": A Leechian Perspective - Ruri Supatmi; Rangga Mega Putra (Litteratura: Jurnal Bahasa dan Sastra, 2026)
This study investigates the types of meaning found in Bruno Mars' Talking to the Moon using Geoffrey Leech's theory of meaning. The research employed a descriptive qualitative approach, with the song lyrics serving as the primary data source. Data were collected through documentation techniques and analyzed using the interactive model proposed by Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The findings revealed that four types of meaning were identified in the lyrics, namely conceptual meaning, connotative meaning, affective meaning, and social meaning. Among these categories, connotative meaning appeared most frequently. This suggests that the songwriter tends to express emotional experiences through symbolic and figurative language rather than direct statements. The use of expressions related to longing, hope, and emotional distance allows listeners to interpret the song in ways that connect with their own experiences. The study also highlights that song lyrics can serve as valuable linguistic resources for understanding how language conveys feelings and personal realities. Despite being limited to a single song, this research contributes to semantic studies by demonstrating the relevance of Leech's theory in analyzing contemporary popular music. Keywords: semantics, types of meaning, Geoffrey Leech, song lyrics, Talking to the Moon (Bruno Mars).